THE IMPLEMENTATION OF PICTURE SERIES AS AN ALTERNATIVE MEDIA FOR TEACHING PAST TENSE IN SPEAKING CLASS - System, Administrator; -, Komang Dian Puspita Candra (Sphota : Jurnal Linguistik dan Sastra, 2014)
ABSTRACT   The purposes of this research is to find out if there is a significant difference between speaking ability of the second semester?s students in class C of STIBA Saraswati Denpasar, taught by and without picture series as an alternative media for teaching past tense in speaking class. This study was designed in the form of classroom action research to 27 students that consists of one cycle and involving four steps in it namely planning, action, observation and reflection. In order to collect the data, three instruments were used those are test, observation and questioner. The data were analyzed qualitative and quantitative based on theory proposed by Brown (2001) and Nurgiyantoro (2010). The data analyses were presented in the table and chart as well as also in descriptive narrative sentences. The result of the quantitative and qualitative data showed that the use of this media could improve the ability of students in learning simple past tense. It could be seen from the process and product result. Talking about the process, the participation of students in the class was increased. The product result have different class mean from pre test 68,18 becomes 83,88 in the first cycle. There are 17 students (62,96%) who passed the indicator remark for speaking assesment in pre test and there is a significant increasing in first cycle becomes 26 students (96,29%).   Key words: speaking, picture series, media, past tense, teaching, learning